Control of waste rock-tailings paste backfill for active mining subsidence areas. (10th January 2018) - Sun, Wei; Wang, Hongjiang; Hou, Kepeng
Abstract: Serious damages to the environment due to surface subsidence and solid wastes are major disasters that occur in metal mines in China. The large-scale application of surface stacking of tailing pastes can possibly control active mining subsidence area in mines. In this paper, an approach was proposed to prepare the solid wastes of mines as the paste, which would be transferred to the subsidence area for backfilling to achieve integrated control of solid wastes and subsidence areas. A backfilling plan that features "horizontal partition and vertical stratification" was developed for subsidence areas. The influencing factors and patterns for the working performance of the backfill, namely strength, fluidity, permeability, and disintegration features, were investigated to prevent secondary disasters, such as the sudden collapses of backfill, downhole debris flow, and ore dilution and loss after control. The process parameters of the surface backfill in Tong Keng mines were determined as follows. The mass concentration of backfilling paste was 81%–83%, the added amount of waste rock was 25%–30%, the amount of added cement was 2%–5%, the 28-day uniaxial compressive strength was 1.5–3.0 MPa, and the permeability coefficient was 10 −4 to 10 −3  cm/s. Graphical abstract: Highlights: A novel approach of using paste was proposed to control the active subsidence areas at mines. A new control measure of "horizontal partition and vertical stratification" was proposed for active subsidence areas. The influencing factors of the backfill of active subsidence areas were investigated. The backfilling parameters for the active subsidence areas at Tong Keng mine were determined.